Antibiotic stewardship through clinical data digitization: perceived opportunities and obstructions by medical doctors from semi-urban setting in central India - Kanthali, Mala; Bhagwat, Gautam; Pathak, Ashish; Purohit, Manju (Frontiers in Digital Health, 2025)
BackgroundAntibiotic resistance is a global public health concern. Inadequate record-keeping and irrational antibiotic prescriptions are challenging factors for antibiotic stewardship. This study explores the perceptions of medical doctors in a semi-urban setting in India, regarding the role of clinical data digitization in mitigating antibiotic resistance.MethodsThe study was conducted at R D Gardi Medical College located in a semi-urban district of Central India. Qualitative data from 20 medical doctors from government and private sector were collected through in-depth, semi-structured interviews of which 18 interviews were analyzed using thematic analysis following Braun and Clarke's framework.ResultsTwo major themes emerged from four overarching subthemes: (1) digitization enhances accountability and continuity of care, (2) potential for local antimicrobial surveillance, (3) infrastructural and technological barriers to adoption, and (4) the necessity of government support and capacity building. The participants believe that digitization could help in rational antibiotic prescription if there is a government mandate and infrastructure feasibility in resource constrained settings.ConclusionClinicians in semi-urban India perceive the digitization of clinical data as a promising tool to combat antibiotic resistance. However, systemic and infrastructural challenges must be addressed to utilize its full potential.